2002
DOI: 10.1016/s0029-7844(01)01754-9
|View full text |Cite
|
Sign up to set email alerts
|

Antepartum, intrapartum, and neonatal significance of exercise on healthy low-risk pregnant working women

Abstract: Exercise in working women is associated with smaller babies, increased number of inductions and augmentations of labor, and longer labors. Colds and flu are more frequent in exercising women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
64
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 15 publications
4
64
0
2
Order By: Relevance
“…Our findings are in agreement with some previous observational findings but not with others [5, 21, 2729, 44, 45], and in disagreement with a randomized controlled trial by Barakat et al [46]. Barakat et al study included 142 women of low to middle socioeconomic position, and it may be expected that women who agree to randomization of their lifestyle during pregnancy constitute a selected group.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our findings are in agreement with some previous observational findings but not with others [5, 21, 2729, 44, 45], and in disagreement with a randomized controlled trial by Barakat et al [46]. Barakat et al study included 142 women of low to middle socioeconomic position, and it may be expected that women who agree to randomization of their lifestyle during pregnancy constitute a selected group.…”
Section: Discussionsupporting
confidence: 86%
“…Barakat et al study included 142 women of low to middle socioeconomic position, and it may be expected that women who agree to randomization of their lifestyle during pregnancy constitute a selected group. Further, some of the observational studies included both elective and emergency C-section [27, 45, 47]; in the present study elective C-sections were excluded. This reduces comparability with part of the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in women’s attitude about exercise between miscarriage groups may be due to elevated levels of anxiety in early pregnancy related to the fear of having another miscarriage and the common misconception that perinatal exercise behavior can lead to miscarriage (Clarke and Gross, 2004; Evenson et al, 2009; Hanghøj, 2013). However, there is limited evidence to support this claim; the majority of studies examining miscarriage and perinatal exercise have found that the risk is no higher for active pregnant women than for inactive pregnant women (Clapp, 1989; Maconochie et al, 2007; Magann et al, 2002; Schlüssel et al, 2008). Given the elevated depressive/anxiety symptoms among women with a history of miscarriage, promoting exercise as a way to improve perinatal mental health may help to improve the exercise attitudes of pregnant women (Da Costa et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Narendren 18 and Magann 16,17 each separated urgent/emergent from planned/elective cesareans, but these are still heterogeneous groups; a pregnant woman might have a cesarean birth for any one of a large number of indications (e.g., umbilical cord prolapse, twins, previous cesarean, fetal distress, etc.). If PA does affect cesarean risk, it is unlikely that all such pathways are involved.…”
Section: Discussionmentioning
confidence: 99%
“…9 Twenty-four previous studies have examined the association between PA or exercise during pregnancy and risk or odds of cesarean. 10–33 Reported effect estimates are not consistent across studies, with the slightly more than half reporting a decreased risk 1932 of cesarean with higher levels of PA or exercise, but with a sizeable minority reporting no effect 10,1214 , an increased risk 15–17,19 , decreased risk in one subgroup only 11 , or decreased risk of elective/planned cesareans but increased risk of urgent/emergent surgeries. 18 …”
mentioning
confidence: 98%